2005
DOI: 10.1097/01.prs.0000176893.44656.8e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Perineurial Repair and Inhibition of Nerve Adhesion by Viscous Injectable Pure Alginate Sol

Abstract: Viscous injectable pure alginate sol inhibited adhesion formation around nerves and enhanced regeneration of the perineurium with barrier function. Because excessive perineurial fibrosis and tethering at the neurolysis or neurorrhaphy site is a common postoperative problem in peripheral nerve surgery, viscous injectable pure alginate sol appears to have potentially broad clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 14 publications
0
32
0
1
Order By: Relevance
“…In addition to its high residence time, alginate is known to significantly inhibit the expression of pro-inflammatory cytokines such as interleukin-1β and tumor necrosis factor α, supporting a potential role in downregulating the inflammatory response at the wound site [28]. Experimental evidence has also revealed that β-D mannuronic acid, a constituent of alginate, acts as a novel non-steroidal drug, attenuating inflammatory reactions [29]. Despite better characteristics in this respect, the gel did not outperform most barriers regarding prevention of adhesion reformation.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to its high residence time, alginate is known to significantly inhibit the expression of pro-inflammatory cytokines such as interleukin-1β and tumor necrosis factor α, supporting a potential role in downregulating the inflammatory response at the wound site [28]. Experimental evidence has also revealed that β-D mannuronic acid, a constituent of alginate, acts as a novel non-steroidal drug, attenuating inflammatory reactions [29]. Despite better characteristics in this respect, the gel did not outperform most barriers regarding prevention of adhesion reformation.…”
Section: Discussionmentioning
confidence: 97%
“…Six weeks after surgery, 48 nerves ( n = 9 in each operated group, and n = 12 in the Normal group) were subjected to biomechanical testing to assess ultimate breaking strength using a published method 11. Briefly, sciatic nerves were exposed under anesthesia, and transected 5 mm proximal to the site of neurolysis.…”
Section: Methodsmentioning
confidence: 99%
“…The rational development and use of chemical compounds to prevent postoperative scarring has recently become possible. Sodium hyaluronan (Artz®; Seikagaku, Tokyo), a polyglycan ester gel (Adcon‐T/N; Gliatech, Cleveland, OH), pure alginate solution (Kuraray Medical, Tokyo), and autocross‐linked polysaccharide gel (Hyaloglide®; Fidia Advanced Biopolymers, Abano Terme, Italy) have all shown promise for preventing postoperative fibrosis in animal models 5, 9–12. However, cases of cerebrospinal fluid leakage after the use of carbohydrate polymer gel in spinal surgery have been reported 13.…”
mentioning
confidence: 99%
“…To stimulate local fibrotic response around the nerve, the surface of the biceps femoris muscle-composing neural bed was repeatedly burned using an electrocoagulator while the exposed nerves were gently retracted and protected. 11 After neurolysis, the right nerve was wrapped with a 1-cm 2 piece of honeycomb film (group H) (Fig. 2), while the left nerve was left untreated as a control (group C).…”
Section: Methodsmentioning
confidence: 99%